A Java typestate checker supporting inheritance - Bacchiani, Lorenzo (2022)
This work was partially supported by the EU H2020 RISE programme under the Marie Skłodowska-Curie grant agreement No. 778233 (BehAPI) and by NOVA LINCS UIDB/04516/2020/TRA/BIM/07 ) via the Portuguese Fundação para a Ciência e a Tecnologia. Publisher Copyright: © 2022 Elsevier B.V.